Pendampingan Kemampuan Menulis Pegon Bagi Santri Madrasah Diniah Takmiliyah Awwaliyah Nurussalam Kelas 1 dan 2 di Pondok Pesantren Sunan Drajat 9 Kowang Semanding Tuban - M. Fathor Rohman; Dewi Mar’atus Sholikhah; Lailul Mufidah; Dhiyaul Fatihah; Ahmad Arif Satria; Agung Maulana (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Talking about pesantren is something that will never end, regarding Islamic boarding schools, of course, it cannot be separated from the madrasah diniah. Madrasah diniah is an educational institution in which students learn many things, such as the yellow book. Every Madrasah diniah institution has a very large potential asset, as well as Madrasah Diniyah Takmiliyah Awwaliyah Nurussalam. The assets owned by Madrasah Diniyah Takmiliyah Awwaliyah Nurussalam have not been fully developed. Through mentoring activities at Madrasah Diniyah Takmiliyah Awwaliyah Nurussalam which uses the ABCD (Asset Base Community Development) method in exploring potential assets, students are able to write pegon according to the rules of writing Arabic pegon. Excavation of assets at Madrasah Diniyah Takmiliyah Awwaliyah Nurussalam through interviews and observations. Mentoring aims to equip students with the ability to write Arabic Pegon fluently to interpret the yellow book. The results of the acquisition in mentoring activities are that students are able to write Arabic Pegon properly and correctly. Because the ability to write Arabic pegon is a must for students of Madrasah Dinah in Islamic boarding schools.